Prosocial Tendencies among Chinese American Children in Immigrant Families: Links to Cultural and Socio‐demographic Factors and Psychological Adjustment. Issue 1 (24th February 2016) - Main, Alexandra; Zhou, Qing; Liew, Jeffrey; Lee, Charlene
Abstract: The present study examined relations between prosocial tendencies (dispositional sympathy and prosocial behavior) and psychological adjustment using a multi‐method and multi‐informant approach in a socioeconomically diverse sample of first‐ and second‐generation Chinese American children from immigrant families (N = 238, M age = 9.2 years). We tested the concurrent associations between: (a) children's dispositional sympathy (rated by parents, teachers, and children, and observed prosocial behavior), (b) psychological adjustment (parent‐ and teacher‐reported externalizing problems and social competence); and (c) cultural and socio‐demographic factors (children's Chinese and American orientations, family Socioeconomic Status (SES), only child status, and children's age, sex, and social desirability). Results from correlations and structural equation modeling suggested that different measures of prosocial tendencies related differently to children's psychological adjustment. Parent‐ and teacher‐rated sympathy were associated with higher child social competence and lower externalizing problems within, but not across, reporter. By contrast, child‐rated sympathy was associated with higher teacher‐rated social competence, and observed prize donation was associated with lower teacher‐rated externalizing problems. Different measures of prosocial tendencies also showed different relations to cultural and socio‐demographic factors. These findings suggest that prosocial tendencies are not a unitary construct in Chinese American immigrant children: the manifestations of prosocial tendencies and their adjustment implications might depend on the context and/or targets of these tendencies.